Roles of Autophagy in Elimination of Intracellular Bacterial Pathogens - Jo, Eun-Kyeong; Yuk, Jae-Min; Shin, Dong-Min; Sasakawa, Chihiro (Frontiers in Immunology, 2013)
As a fundamental intracellular catabolic process, autophagy is important and required for the elimination of protein aggregates and damaged cytosolic organelles during a variety of stress conditions. Autophagy is now being recognized as an essential component of innate immunity; i.e., the recognition, selective targeting, and elimination of microbes. Because of its crucial roles in the innate immune system, therapeutic targeting of bacteria by means of autophagy activation may prove a useful strategy to combat intracellular infections. However, important questions remain, including which molecules are critical in bacterial targeting by autophagy, and which mechanisms are involved in autophagic clearance of intracellular microbes. In this review, we discuss the roles of antibacterial autophagy in intracellular bacterial infections (Mycobacteria, Salmonella, Shigella, Listeria, and Legionella) and present recent evidence in support of molecular mechanisms driving autophagy to target bacteria and eliminate invading pathogens.